Penerapan Sanksi Pasal 279 Kitab Undang-Undang Hukum Pidana Terhadap Tindak Pidana Kejahatan Asal Usul Perkawinan Dalam Kasus Poligami Terhadap Pernikahan Siri - M. Fadhillah Johar; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The violation of the origin of marriage was felonies which could have a negative impact to Indonesian people. Many state officials were doing the violation of the origin of marriage to fulfil their desires and eagerness to remarriage by way of polygamy through unregistered marriage. The objective of the research was first, to know the implementation of sanction of article 279 of penal code about the violation of the origin of marriage againts the unregistered marriage. Second, to know whether the unregistered marriage can be criminalized.Writing this research uses normative law research that examines the legislation and the principles of law, Marriage Law No. 1 of 1974 and the legislation of penal code in Indonesia. This research had a descriptive nature, which was a form of research that aimed to an overview of the problem. Source of data used was secondary data consists of primary, secondary and tertiary legal materials. The gathered data were analyzed by literature studies or study documents such as books, magazines, journals and the legislation in force. Thus, this study has the relationship between the data contained either in the legislation or in the literature.From the result of the research, there were two main points could be inferred. First, the unregistrated marriage of polygamy was felonies which could be categorized into the violation of the origin of marriage, therefore people who commited unregistrated marriage of polygamy must be held accountable. Second, the unregistrated marriage could be criminalized, because the marriage was not registered under the terms of legislation, thus this was the violation of laws. However, the criminalization of unregistrated marriage was not make the marriage “haram” in islamic belief, the marriage would be valid as long as its fulfilled the requirements.Key Word : The Violation of the Origin of Marriage – Polygamy – Unregistered Marriage